Innovating education: AI-powered self-instructional materials for the Moodle platform - Mohd Yatim, Siti Ainor; Ramli, Nurulhuda; Abdul Hamid, Hazrul; Mansor, Mohd Asyraf (Academica Press Solutions, 2025)
This innovative Self-Instructional Material (SIM) for Linear Algebra, seamlessly integrated into the Moodle platform, offers students a flexible and accessible learning experience. Designed initially for Open and Distance Learning at Universiti Sains Malaysia, the AI-powered SIM enables self-paced and self-directed learning, catering to diverse learning needs and preferences. It provides self-explanatory, self-contained, and selfmotivating resources, empowering students to take control of their learning journey. This approach addresses access to quality education challenges, particularly for students in remote or underserved communities. The SIM utilizes AI algorithms to personalize learning paths, adapt to individual student pacing, and offer interactive tutorials, adaptive quizzes, and real-time feedback. Technology integration transforms traditional educational paradigms, providing students worldwide with unparalleled access to high-quality learning experiences in Linear Algebra.